The Impact of EFL Teachers’ Open-Mindedness and Immediacy on Their Social Intelligence: A Theoretical Review - Cui, Zhan (Frontiers in Psychology, 2022)
The role of psycho-emotional and social factors in determining teachers’ pedagogical success has been largely endorsed in the literature. This highlights the necessity of improving EFL teachers’ awareness and knowledge of various factors related to classroom interaction and interpersonal communication. Despite the existence of some L2 studies on interpersonal communication skills after the popularity of positive psychology, the interplay of variables that directly reflect classroom interactions and their linkage to one’s intelligence(s) has been overlooked, to date. To fill this gap, the present mini review presented the theoretical and empirical foundations of three significant teacher-related variables, namely open-mindedness, immediacy, and social intelligence. In so doing, their relevant definitions, conceptualizations, models, and correlates were provided. Finally, the study offered some practical implications and suggestions for EFL stakeholders and researchers who can improve their knowledge and use of social-based variables in second/foreign language education.